3 - Le cinéma, un véhicule culturel en contexte colonial - Odile Goerg, (Afrika Zamani, 2022)
In the colonies, and later on in independent countries, a movie theater stands as a bank of images and as a replay scene for interpersonal relationships. Moving pictures help establish a dialogue with the outer world, to interact with the unknown beyond the symbolic elements that can be recycled locally. This is all the more true with the fragments of Western, Indian films, Egyptian comedies that circulate... and more recently Bollywood movies that convey songs, attitudes, dialogues whose impact is yet to be measured.